Is the Posterior Approach With Posterior locking compression plate and Anterior Allograft Useful and Safe in the Treatment of Periprosthetic Humeral Fractures Following Reverse Total Shoulder Arthroplasty?. (11th February 2022) - Vicenti, Giovanni; Solarino, Giuseppe; Carrozzo, Massimiliano; Simone, Filippo; Ottaviani, Guglielmo; Bizzoca, Davide; Zavattini, Giacomo; Zaccari, Domenico; Buono, Claudio; Moretti, Biagio
Introduction: As the reverse total shoulder arthroplasty (RTSA) surgery has dramatically increased in the last few decades, many complications have followed through. The periprosthetic fracture, at the moment, is still a subject of debate in the orthopedic world. In this monocentric study, along with a literature review of periprosthetic humeral fractures, we would present our institutional experience with the treatment of periprosthetic humeral fractures with a posterior humeral approach, posterior cortex plate fixation, anterior strut allograft, screws, and cerclage wires. Materials and Methods: Our study consisted in a prospective monocentric study based on 18 patients, with a mean age of 75.3 years (range 64–88), all following a reverse shoulder total arthroplasty (RTSA). Postoperative follow-ups were taken at 1, 6, and 12 months with objective measurement of shoulder motion and strength, while clinical outcome measures were assessed using the American Shoulder and Elbow Surgeons (ASES score) and visual analog scale (VAS) for pain. Together with that, we performed a literature review focused on the management of periprosthetic humeral fractures after shoulder arthroplasty. Results: All fractures consolidated without complication at a mean 4.2 months (range 3–6). At final follow-up, the average active shoulder flexion was 88° (range 62–129°), active abduction 73° (range 52–91°) and active external rotation 22° (range 3–56°). The average ASES score was 73 (range 59–97), while average VAS score was 1.1 (range 0–3). Discussion: Surgical treatment of periprosthetic humeral fractures following a shoulder arthroplasty remains a hard challenge for every surgeon, and their treatment must consider fracture's location, displacement, and local bone quality. Conclusions: The posterior approach with a posterior plate placement and anterior strut allograft, which is appliable only in case of a B or C type fracture according to Worland classification, could be a good treatment option for periprosthetic humeral fractures.